2020
DOI: 10.1136/jitc-2019-000234
|View full text |Cite|
|
Sign up to set email alerts
|

C reactive protein impairs adaptive immunity in immune cells of patients with melanoma

Abstract: BackgroundHigh C reactive protein (CRP) levels have been reported to be associated with a poor clinical outcome in a number of malignancies and with programmed cell death protein 1 immune checkpoint blockade in patients with advanced cancer. Little is known about the direct effects of CRP on adaptive immunity in cancer. Therefore, we investigated how CRP impacted the function of T cells and dendritic cells (DCs) from patients with melanoma.MethodsThe effects of CRP on proliferation, function, gene expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 44 publications
2
59
1
Order By: Relevance
“…Baseline CRP was also associated with poor OS in both cohorts of Checkmate-064. 35 Open access Baseline N/L ratio was associated with survival in the Checkmate-066 and Checkmate-067 studies in a multivariable analysis and was highly correlated with IL-6 and CRP.…”
Section: Statistical Analysesmentioning
confidence: 96%
“…Baseline CRP was also associated with poor OS in both cohorts of Checkmate-064. 35 Open access Baseline N/L ratio was associated with survival in the Checkmate-066 and Checkmate-067 studies in a multivariable analysis and was highly correlated with IL-6 and CRP.…”
Section: Statistical Analysesmentioning
confidence: 96%
“…Tumor in ltration by CD8 + T cells has been strongly associated with survival of cancer patients [26,28]. Yoshida et al also reported that CRP inhibited proliferation, activation, and function of CD8 + T cells in patients with melanoma [40]. Thus, CD8 + TILs may be more strongly associated with LCR, which is a robust prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside, ROS-mediated disruption of mitochondrial-membrane exposes cardiolipin and mtDNA to cytosol thus provoking NLRP3 to compose inflammasome ( Iyer et al, 2013 ). C-reactive proteins are elevated following OP exposure and higher levels of this inflammatory marker can contribute to immunosuppression ( Yoshida et al, 2020 ; Taghavian et al, 2016 ). IFN constitutes the first line of defense against viral infections ( Ivashkiv & Donlin, 2014 ).…”
Section: Mechanism Of Immunotoxicity: Ops Versus Sars-cov-2mentioning
confidence: 99%